Analysis of SAPRC16 chemical mechanism for ambient simulations. (November 2018) - Venecek, Melissa A.; Cai, Chenxia; Kaduwela, Ajith; Avise, Jeremy; Carter, William P.L.; Kleeman, Michael J.
Abstract: SAPRC16 is an interim update to the SAPRC series of chemical mechanisms that includes updated rate constants, a revised representation of radical chemistry, and a new speciation lumping scheme to better develop predictions of SOA precursors. In this study, the ability of the SAPRC16 chemical mechanism to simulate regional ozone episodes is tested in seven (7) major cities across the United States. The UCD-CIT 3-dimensional (3D) airshed model was configured with both SAPRC11 (base mechanism) and SAPRC16 (updated mechanism). Concentrations of ozone, hydroxyl radical (OH) and hydroperoxyl (HO2 ) radical predicted with both mechanisms were compared to measured values. It was generally observed that SAPRC16 predicts slightly lower ozone concentrations than SAPRC11 in NOx rich urban centers. A box model analysis shows that the SAPRC16 mechanism quenches ozone production earlier than SAPRC11 as NOx concentrations increase (yielding decreasing VOC/NOx ratios). This could be caused by more detailed HO2 +RO2 reactions and RO2 isomerization reactions in SAPRC16 that compete with the HO2 +NO reaction. Predictions from SAPRC11 are in better agreement with the measurements in the western United States, however SAPRC16 outperforms SAPRC11 in some eastern and southern U.S. cities. These results may also be strongly influenced by the accuracy of emissions inventories in each region. Differences in ozone concentrations predicted by SAPRC16 and SAPRC11 increased as emissions decreased suggesting that the two mechanisms will predict different outcomes from future emissions control programs. In general, the SAPRC11 mechanisms slightly over-predicts OH concentration while under-predicting HO2 radical concentration and the SAPRC16 mechanism slightly under predicts OH and under predicts HO2, sometimes by large amounts. The reasons for this behavior are unknown at this time. These features will influence the secondary organic aerosol (SOA) predictions from each mechanism since the branching between high NOx and low NOx regimes depends on calculated HO2 concentrations. Further analysis of the HO2 +RO2 reactions and RO2 isomerization reactions and the reasons for the lower HO2 predictions in the updated SAPRC16 chemical mechanism should be carried out before widespread adoption of the new mechanism. Highlights: SAPRC16 was compared to SAPRC11 in a box model and two regional chemical transport models applied across the United States. SAPRC16 and SAPRC11 predict different ozone and peroxy-radical concentrations under 2010 conditions. SAPRC16 and SAPRC11 predict different response in ozone and peroxy-radical concentrations when NOx and VOC levels change. Further study is needed to understand the behavior of SAPRC16.